A description of essential service delivery: a case study of Makwarela Town in Thulamela Municpality of the Limpopo Province - Tshirado, Ndiafhi (My University, 2004)
Refer to document
Thesis (M.Dev.) --University of Limpopo, 2004
Keywords: Service delivery; Municipalities; Municipal services -- South Africa -- Limpopo; Local government -- South Africa -- Limpopo